(untitled) (Journal of the College of Education for Women, 2019)
Soil is considered one of the main factors of subsidence phenomena whichbecame continually happen in Baghdad (Ghazalia, Ameria, and Hay al-Amyl)causing bad effects as shortage of drinking water, traffic jam and formationswamps.This thesis depends on soil study to a depth 15 meters, due to itsimportance in subsidence. This done through specifying its chemical physicalproperties.Soil within Iraq climate, in case of water stopping for any reason it contractand shrink away especially when it exposed to high pressure these factorsfinally caused subsidence. In case of leakage underground water or that ofdamaged water pipes this will contribute to chemical reactions which damage soilstructure and increasing solidity and liquidity of higher layers and sand washingof lower areas of soil.In case of stopping this leakage and dryness in the hot area will lead tocontract and shrink away the liquid soil and subsidence the upper layers. Thestudy reached that soil is a main factor behind this phenomenon.